PENGARUH KUALITAS PRODUK, STORE ATMOSPHERE, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK BATIK SOGA (STUDI PADA KAMPUNG BATIK LAWEYAN SURAKARTA) - Pertiwi, Heppy Atma; Jaelani, Jaelani; Susilowati, Heni; Hargyatni, Titin (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine and analyze the direct influence of lifestyle on product purchasing decisions at Kampung Batik Laweyan Surakarta, to determine and analyze the direct influence of store atmosphere on product purchasing decisions at Kampung Batik Laweyan Surakarta, to determine and analyze the direct influence of product value on product purchasing decisions at Kampung Batik Laweyan Surakarta and to determine and analyze the simultaneous influence of lifestyle, store atmosphere, product value on product purchasing decisions at Kampung Batik Laweyan Surakarta. This study uses a quantitative method with a sample of 50 consumer respondents at Kampung Batik Laweyan Surakarta. Data were analyzed using validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, normality tests, multiple linear regression analysis tests, T tests, F tests, R2 determination coefficient tests using IBM SPSS Statistics. The results of the study indicate that lifestyle directly has a significant effect on product purchasing decisions for consumers at Kampung Batik Laweyan Surakarta, product value directly has a significant effect on product purchasing decisions for consumers at Kampung Batik Laweyan Surakarta, store atmosphere have a significant effect on product purchasing decisions for consumers at Kampung Batik Laweyan Surakarta, and directly and simultaneously lifestyle, store atmosphere, and product value have a significant effect on consumer product purchasing decisions at Kampung Batik Laweyan Surakarta.